2012
DOI: 10.3945/jn.112.163253
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Alkylresorcinols, Biomarkers of Whole-Grain Intake, Are Related to Lower BMI in Older Adults

Abstract: Alkylresorcinols (AR) are phenolic lipids found in the bran fraction of whole-grain wheat, rye, and barley. In intervention studies, plasma AR concentration increased in response to greater intakes of whole grain, wheat, and rye. This study examined the cross-sectional associations between plasma AR and habitual whole-grain intake, BMI, and metabolic risk factors in 407 free-living older adults (166 men and 241 women; aged 60-81y; median BMI: 27 kg/m 2 ). Plasma AR were measured by liquid chromatography-tandem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
19
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
4
2

Relationship

1
9

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 41 publications
(61 reference statements)
2
19
0
Order By: Relevance
“…However, plasma AR concentrations can probably be used to distinguish between lowand high-WG consumers with sufficient precision in populations with a regular and frequent WG wheat and rye intake (38). This was verified in recent epidemiologic studies in which plasma ARs were successfully used as a proxy of WG intake in relation to colorectal cancer and body weight (42,43). The modest reproducibility of plasma AR concentration is partly because ARs reflect short-to medium-term intake and because of substantial day-to-day variation in WG intake as evidenced by the observed reproducbility of WG intake (ICC = 0.60).…”
Section: Discussionmentioning
confidence: 93%
“…However, plasma AR concentrations can probably be used to distinguish between lowand high-WG consumers with sufficient precision in populations with a regular and frequent WG wheat and rye intake (38). This was verified in recent epidemiologic studies in which plasma ARs were successfully used as a proxy of WG intake in relation to colorectal cancer and body weight (42,43). The modest reproducibility of plasma AR concentration is partly because ARs reflect short-to medium-term intake and because of substantial day-to-day variation in WG intake as evidenced by the observed reproducbility of WG intake (ICC = 0.60).…”
Section: Discussionmentioning
confidence: 93%
“…However, the sample size is relatively large, and the reproducibility of the Swedish part of the study has been shown to be adequate (44). Plasma alkylresorcinol concentrations are to some extent affected by other factors than whole-grain intake, such as sex, age, and BMI (44,(47)(48)(49)(50)(51). We carefully adjusted or matched on these factors, but residual confounding cannot be ruled out.…”
Section: Discussionmentioning
confidence: 97%
“…Hence, intake of the important ND components canola oil and fatty fish can be assessed by determining blood concentrations of a-linolenic acid (18:3n-3) (12) and the long-chain n-3 FA EPA (20:5n-3) and DHA (22:6n-3) (13), respectively, whereas divergence from the prescribed low-fat dairy intake may be reflected by pentadecanoic acid (15:0) (14). Intake of wholegrain wheat and rye, important components of the ND, can be assessed by plasma alkylresorcinol concentrations (15)(16)(17). Certain fruits and vegetables are rich in b-carotene, so this carotenoid was suggested as a DB of fruit and vegetables, which are other major components of the ND (18).…”
Section: Introductionmentioning
confidence: 99%